2009
DOI: 10.3390/medicina45100100
|View full text |Cite
|
Sign up to set email alerts
|

Epidural and general anesthesia versus general anesthesia in radical prostatectomy

Abstract: Induced hypotension with epidural anesthesia influences the intraoperative blood loss in prostate cancer patients undergoing radical prostatectomy. The aim of this study was to evaluate intraoperative blood loss and need of blood transfusions in patients who underwent radical prostatectomy under epidural/general anesthesia and general anesthesia. Two groups were selected: epidural/general anesthesia group (study group, 27 patients) received epidural anesthesia in association with general anesthesia, and genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
3
11
0
1
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20][21] Pooling the results to produce a meta-analysis was not possible. The decision not to perform a meta-analysis took into account the fact that the interventions and outcomes assessed were different among the RCTs included.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[11][12][13][14][15][16][17][18][19][20][21] Pooling the results to produce a meta-analysis was not possible. The decision not to perform a meta-analysis took into account the fact that the interventions and outcomes assessed were different among the RCTs included.…”
Section: Discussionmentioning
confidence: 99%
“…Tikuisis et al 12 reported the mean without standard deviation; O'Connor et al 13 reported the number of patients who received blood transfusion; Ozyuvaci et al 14 reported this outcome for radical cystectomy; Salonia et al 15 reported autologous and heterologous blood transfusions; and the data from Shir et al, 18 Hendolin et al 20 and McGowan et al 21 were not taken into consideration because the anesthetic technique used was not the same as used today. Hendolin et al 20 used sodium thiopental, succinylcholine and alcuronium.The basilic vein was used for venous pressure measurement, and the left radial artery was cannulated for blood gas measurement.…”
Section: Blood Transfusion Requirementsmentioning
confidence: 99%
See 3 more Smart Citations